Sulforaphane counteracts aggressiveness of pancreatic cancer driven by dysregulated Cx43-mediated gap junctional intercellular communication - Forster, Tobias; Rausch, Vanessa; Zhang, Yiyao; Isayev, Orkhan; Heilmann, Katharina; Schönsiegel, Frank; Liu, Li; Neßling, Michelle; Richter, Karsten; Labsch, Sabrina Daniela; Nwaeburu, Clifford C.; Mattern, Jürgen; et al. (OncoTarget, 2014)
The extreme aggressiveness of pancreatic ductal adenocarcinoma (PDA) has been - associated with blocked gap junctional intercellular communication (GJIC) and the - presence of cancer stem cells (CSCs). We examined whether disturbed GJIC is - responsible for a CSC phenotype in established and primary cancer cells and patient - tissue of PDA using interdisciplinary methods based in physiology, cell and molecular - biology, histology and epigenetics. Flux of fluorescent dyes and gemcitabine through - gap junctions (GJs) was intact in less aggressive cells but not in highly malignant - cells with morphological dysfunctional GJs. Among several connexins, only Cx43 was - expressed on the cell surface of less aggressive and GJIC-competent cells, whereas - Cx43 surface expression was absent in highly malignant, E-cadherin-negative and - GJIC-incompetent cells. The levels of total Cx43 protein and Cx43 phosphorylated at - Ser368 and Ser279/282 were high in normal tissue but low to absent in malignant - tissue. si-RNA-mediated inhibition of Cx43 expression in GJIC-competent cells - prevented GJIC and induced colony formation and the expression of stem cell-related - factors. The bioactive substance sulforaphane enhanced Cx43 and E-cadherin levels, - inhibited the CSC markers c-Met and CD133, improved the functional morphology of GJs - and enhanced GJIC. Sulforaphane altered the phosphorylation of several kinases and - their substrates and inhibition of GSK3, JNK and PKC prevented sulforaphane-induced - CX43 expression. The sulforaphane-mediated expression of Cx43 was not correlated with - enhanced Cx43 RNA expression, acetylated histone binding and Cx43 promoter - de-methylation, suggesting that posttranslational phosphorylation is the dominant - regulatory mechanism. Together, the absence of Cx43 prevents GJIC and enhances - aggressiveness, whereas sulforaphane counteracts this process, and our findings - highlight dietary co-treatment as a viable treatment option for PDA.
Gesehen am 11.08.2020